Oscillation between hyperthyroidism and hypothyroidism in an adolescent female with Graves' disease - Lee, Yee Lin (A S E A N Federation of Endocrine Societies, 2025)
Graves’ disease (GD) presenting as fluctuating hyperthyroidism and hypothyroidism is a rare phenomenon and poses a diagnostic challenge. A 14-year-old girl with GD, initially thought to have Hashimoto thyroiditis presented with a goiter and oscillating thyroid function over the course of 4 years. This case depicts a case of GD with oscillating thyroid function and stresses the importance of TSH receptor antibodies (TRAb) in the evaluation of patients with hyperthyroidism without Graves’ ophthalmopathy.